If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 480 = -10(-6x + -6) Reorder the terms: 480 = -10(-6 + -6x) 480 = (-6 * -10 + -6x * -10) 480 = (60 + 60x) Solving 480 = 60 + 60x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60x' to each side of the equation. 480 + -60x = 60 + 60x + -60x Combine like terms: 60x + -60x = 0 480 + -60x = 60 + 0 480 + -60x = 60 Add '-480' to each side of the equation. 480 + -480 + -60x = 60 + -480 Combine like terms: 480 + -480 = 0 0 + -60x = 60 + -480 -60x = 60 + -480 Combine like terms: 60 + -480 = -420 -60x = -420 Divide each side by '-60'. x = 7 Simplifying x = 7
| 3x+101-4x-33=108-16x-109 | | =3x+3(x+1)+3(x+2) | | -3f-9=-2f | | -14p-3(2-6p)=2(p-2)-6 | | 4x+12-2x=3x-9 | | (x-2)x=224 | | 7y+4x=42 | | 72=1.5x | | a=1.2(h-84) | | 16h-72b=4h-30 | | 4c+11-7n=-13 | | 1+3x+3=-11 | | h=-4+7t-5t^2 | | 8a=0.48 | | 4xy+6yz-5xz-4xy= | | 33.33x+y=4 | | 5y+12-8y=-42 | | x+(x*.13)=49.15 | | 9-9x=-171 | | 8x=10x-6 | | 8x+7x-4=4x+5x-9 | | 13x-3=x+53 | | 11+7q=12+6q | | 7b+7=6b | | -3+5x-3x=-15 | | -7-2j=5j | | 3k-5-7k=-37 | | 2lnx=21 | | 4x-1=-3x+13 | | 3x+42-5x=2-9x+5 | | X+5x=450 | | X+4+2x=20 |